2020
DOI: 10.1029/2019ja027283
|View full text |Cite
|
Sign up to set email alerts
|

Response of Sporadic E Layer to Sudden Stratospheric Warming Events Observed at Low and Middle Latitudes

Abstract: This paper investigates the variations of middle‐ and low‐latitude sporadic E (Es) layers during 2011–2012 and 2012–2013 sudden stratospheric warming (SSW) events by using observations from six ionosondes in East Asia over China and Japan region. Observations of Es critical frequency (foEs) at all these ionosondes present obvious enhancements around the days of new and full moon during SSW periods. Wavelet spectra of foEs during two SSW events exhibit noticeable enhanced 14.5‐day modulation, which resembles th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…Although the increase of polar stratospheric temperature is large during the SSW event in 2012, the wave power at the 14-15 day period is particularly low during this event, which may be due to a small decrease of the polar stratospheric zonal wind (Tang et al, 2020). Mo and Zhang (2020) showed that the temporal extent of wave power at 14-15 day period is consistent with the temporal extent of the decrease of the stratospheric zonal mean wind rather than the increase of stratospheric temperature during SSW.…”
Section: Results and Analysismentioning
confidence: 77%
See 1 more Smart Citation
“…Although the increase of polar stratospheric temperature is large during the SSW event in 2012, the wave power at the 14-15 day period is particularly low during this event, which may be due to a small decrease of the polar stratospheric zonal wind (Tang et al, 2020). Mo and Zhang (2020) showed that the temporal extent of wave power at 14-15 day period is consistent with the temporal extent of the decrease of the stratospheric zonal mean wind rather than the increase of stratospheric temperature during SSW.…”
Section: Results and Analysismentioning
confidence: 77%
“…It can be seen from Figure 3d that the wave power at the 14–15 day period is particularly large during the SSW period in 2006 and 2009, which can be attributed to the evidence that these two SSW events were stronger and longer than the others events ever recorded (Manney et al., 2010). Although the increase of polar stratospheric temperature is large during the SSW event in 2012, the wave power at the 14–15 day period is particularly low during this event, which may be due to a small decrease of the polar stratospheric zonal wind (Tang et al., 2020). Mo and Zhang (2020) showed that the temporal extent of wave power at 14–15 day period is consistent with the temporal extent of the decrease of the stratospheric zonal mean wind rather than the increase of stratospheric temperature during SSW.…”
Section: Results and Analysismentioning
confidence: 99%
“…During SSW events, the reversal of zonal winds as well as thermal temperature variations in the stratosphere and mesosphere could affect the propagation of lunar tides (Lindzen and Hong, 1974; Stening et al, 1997; Pedatella et al, 2012). The enhancement of the 14.5‐day semimonthly lunar period component in the MLT region, eventually produces variations in the E S layer, shown in Figure 5 (Tang Q et al, 2020).…”
Section: E Region Irregularitymentioning
confidence: 99%
“… The time variations of f o E S spectrum observed by six ionosondes located at Mohe (122.37°E, 53.50°N), Wakkanai (141.75°E, 45.16°N), Kokubunji (139.49°E, 35.71°N), Yamagawa (130.62°E, 31.20°N), Wuhan (114.61°E, 30.53°N), and Okinawa (128.15°E, 26.68°N) during two SSW events. The warming onset is indicated by the red vertical dashed line, while the red horizontal dashed line denotes the 14.5‐day period (after Tang Q et al, 2020). …”
Section: E Region Irregularitymentioning
confidence: 99%
See 1 more Smart Citation